Psychometric Evaluation of the PROMIS® Pediatric Psychological and Physical Stress Experiences Measures. (27th February 2018) - Bevans, Katherine B; Gardner, William; Pajer, Kathleen A; Becker, Brandon; Carle, Adam; Tucker, Carole A; Forrest, Christopher B
Abstract: Objective: To provide psychometric evaluation of the PROMIS ® Pediatric Psychological and Physical Stress Experiences measures. Methods: Across two studies, Psychological and Physical Stress Experiences items were administered to 2, 875 children aged 8–17 years and 2, 212 parents of children aged 5–17 years. Analyses included descriptive statistics, reliability, factor analysis, differential item functioning (DIF), and assessment of construct validity. Items were calibrated using item response theory to estimate item parameters representative of the United States. Recommended eight- and four-item short forms were constructed for child- and parent-report versions of the Psychological and Physical Stress Experiences item banks. Results: Final item banks were unidimensional and items were locally independent and free from impactful DIF. Psychological Stress banks include 19 child-report and 12 parent-proxy items. Physical Stress banks include 26 child-report and 26 parent-proxy items. All instruments have strong internal consistency and retest-reliability, and provide precise estimates of varying stress levels. The instruments' construct validity was evidenced by known-group comparisons and convergence with legacy measures. Conclusions: The Patient Reported Outcome Measurement Information System (PROMIS) Pediatric Psychological and Physical Stress item banks and short forms provide efficient, precise, and valid assessments of children's stress experiences.